Glass Substrate

By controlling the alkali metal oxide content in the glass substrate composition, the challenges of electrostatic charging and manufacturing costs in organic EL displays are addressed, resulting in a glass substrate with improved electrostatic properties and manufacturing efficiency.

JP7654352B2Active Publication Date: 2025-04-01NIPPON ELECTRIC GLASS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2019122939
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-07-01
Publication Date
2025-04-01
Estimated Expiration
2039-07-01

AI Technical Summary

Technical Problem

Glass substrates used in organic EL displays face challenges with electrostatic charging during manufacturing, leading to deviations in film deposition pitch and increased costs due to the need for surface roughening and chemical etching.

Method used

A glass substrate with a controlled composition of alkali metal oxides, specifically limiting Li2O to 0.03% or less, Na2O to 0.001-0.1%, and K2O to 0.001-1%, along with other components like B2O3 and TiO2, to achieve low electrostatic properties and improved manufacturing characteristics.

Benefits of technology

The proposed glass substrate exhibits low electrostatic charging properties, reducing the likelihood of pitch deviations in film deposition and minimizing manufacturing costs by eliminating the need for surface roughening and chemical etching.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654352000006
    Figure 0007654352000006
  • Figure 0007654352000007
    Figure 0007654352000007
  • Figure 0007654352000001
    Figure 0007654352000001
Patent Text Reader

Abstract

To provide a glass substrate having low electrification characteristic.SOLUTION: A glass substrate includes, as a glass composition, not more than 0.03% of Li2O, 0.001-0.1% of Na2O and 0.001-1% of K2O in terms of mass%, and less than 1 of Na2O / K2O in terms of mass ratio.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass substrate, and more particularly to a glass substrate suitable for use as a display substrate in general, including an organic EL display. [Background technology]

[0002] Electronic devices such as organic light-emitting diode (OLED) displays are thin, have excellent video display capabilities, and consume little power, so they are used in applications such as displays for televisions and smartphones.

[0003] Glass substrates are widely used as substrates for organic EL displays. The main requirements for glass substrates for this purpose are as follows: (1) The content of alkali metal oxides is low to prevent diffusion of alkali ions into the semiconductor material formed during the heat treatment process; (2) To reduce the cost of glass substrates, the glass must be highly productive, particularly in terms of resistance to devitrification and melting properties. (3) There is little deformation of the glass substrate due to thermal shrinkage during the manufacturing process of p-Si / a-Si TFTs. (4) The glass substrate has low electrostatic charge during the manufacturing process of p-Si / a-Si TFTs. (5) It has a smooth surface suitable for the p-Si / a-Si TFT manufacturing process. Summary of the Invention [Problem to be solved by the invention]

[0004] To elaborate on (4) and (5) above, since the glass substrate is an insulator, the glass substrate becomes charged when it comes into contact with the exposure stage, etc. during the p-Si / a-Si TFT manufacturing process. This charging is one of the major causes of deviations in the pitch of each film used in TFT pixels.

[0005] As described in (5), a smooth surface is desirable to form high-quality TFTs, and glass substrates used as display substrates are required to have a surface quality close to that of a fairly smooth free surface, even if they are glass substrates produced using a float process that requires polishing. However, the smoother the surface of the glass substrate, the more easily the glass substrate becomes charged. In other words, the issue in (4) is in a trade-off relationship with the issue in (5).

[0006] Currently, the backside of the exposure stage and the glass substrate are roughened to suppress charging, but even if the exposure stage is roughened, the roughened surface will become smooth as it is used repeatedly. In addition, in order to roughen the backside of the glass substrate, chemical etching or gas etching is required, which causes problems such as the inclusion of etching residue on the film formation surface. In addition, the above process must be added to the manufacturing process, which naturally leads to increased costs.

[0007] Furthermore, as displays have become thinner in recent years, the decline in yield due to static electricity has become a major problem. The reason is that as the glass substrate becomes thinner, it fits better with the exposure stage, etc., and as a result, the contact area between the glass substrate and the exposure stage increases, making it more susceptible to static electricity.

[0008] In view of the above, an object of the present invention is to provide a glass substrate that is less prone to electrostatic charging. [Means for solving the problem]

[0009] As a result of repeated various experiments, the present inventors found that the above technical problems can be solved by strictly controlling the content of trace amounts of alkali oxides contained in the glass substrate, and propose this as the present invention. That is, the glass substrate of the present invention is characterized in that it contains, in mass %, 0.03% or less Li2O, 0.001 to 0.1% Na2O, and 0.001 to 1% K2O as a glass composition, and the mass ratio of Na2O / K2O is 1 or less. Here, "Na2O / K2O" is the value obtained by dividing the content of Na2O by the content of K2O.

[0010] The glass substrate of the present invention preferably contains, in mass %, 39% or less of B2O as a glass composition.

[0011] The glass substrate of the present invention preferably contains, in mass %, 2% or less of TiO2 as a glass composition.

[0012] The glass substrate of the present invention preferably has a surface potential after 300 seconds / initial surface potential of 0.8 or less. Here, "surface potential after 300 seconds" refers to the surface potential of the glass substrate after the fluororubber is brought into contact with the glass substrate for 300 seconds. "Initial surface potential" refers to the surface potential of the glass substrate immediately after the fluororubber is brought into contact with the glass substrate. "Surface potential after 300 seconds / initial surface potential" refers to the surface potential after 300 seconds divided by the initial surface potential. The smaller this value, the easier it is for charges to diffuse from the surface of the glass substrate, and the lower the chargeability. A surface potential sensor or the like can be used to measure the surface potential.

[0013] The glass substrate of the present invention preferably has a thermal shrinkage of 30 ppm or less when heat-treated at 500° C. for 1 hour. The "thermal shrinkage when heat-treated at 500° C. for 1 hour" is measured by the following method. First, as shown in FIG. 1(a), a strip-shaped sample G of 160 mm×30 mm is prepared as a measurement sample. Markings M are formed at both ends of the long side direction of the strip-shaped sample G at positions 20 to 40 mm away from the edge using #1000 waterproof abrasive paper. Then, as shown in FIG. 1(b), the strip-shaped sample G on which the markings M are formed is folded in two along the direction perpendicular to the markings M to prepare sample pieces Ga and Gb. Then, only one of the sample pieces Gb is subjected to a heat treatment in which the temperature is raised from room temperature to 500° C. at a rate of 5° C. / min, held at 500° C. for 1 hour, and then cooled at a rate of 5° C. / min. After the above heat treatment, as shown in Figure 1(c), a sample piece Ga that has not been heat treated and a sample piece Gb that has been heat treated are arranged in parallel, and the positional deviation (ΔL1, ΔL2) of the markings M of the two sample pieces Ga and Gb is read using a laser microscope, and the thermal shrinkage rate is calculated using the following formula. Note that 10 mm in the formula below is the initial distance between the markings M. Note that if the thermal shrinkage rate is high, a deviation will occur in the pixel pitch of the TFT, causing display defects.

[0014] Heat shrinkage rate (ppm)=[{ΔL1(μm)+ΔL2(μm)}×10 3 ] / l0(mm)

[0015] The glass substrate of the present invention preferably has a strain point of 700° C. or higher. The "strain point" is a value measured based on the methods of ASTM C336 and C338. The higher the strain point, the less likely thermal shrinkage will occur during the manufacturing process of p-Si TFT.

[0016] The glass substrate of the present invention has an average thermal expansion coefficient of 45×10 -7 / ° C. or less. The "average thermal expansion coefficient at 30 to 380° C." is a value measured with a dilatometer.

[0017] The glass substrate of the present invention preferably has a Young's modulus of at least 73 GPa. "Young's modulus" refers to a value measured based on a dynamic elastic modulus measurement method (resonance method) in accordance with JIS R1602.

[0018] The glass substrate of the present invention has a liquidus viscosity of 10 4.0 The "liquidus viscosity" is the value obtained by placing glass powder that passes through a standard 30 mesh (sieve opening 500 μm) and remains on a 50 mesh (sieve opening 300 μm) in a platinum boat and holding it in a temperature gradient furnace for 24 hours, and measuring the viscosity at the temperature at which crystals (primary phase) precipitate according to the well-known platinum ball pulling method.

[0019] The glass substrate of the present invention preferably has a β-OH value of 0.30 / mm or less. The "β-OH value" refers to a value obtained by measuring the transmittance of glass using FT-IR and using the following formula: β-OH value = (1 / X)log(T1 / T2) X: Glass thickness (mm) T1: Reference wavelength 3846cm -1 Transmittance (%) T2: Hydroxyl group absorption wavelength 3600cm -1 Minimum transmittance (%) near

[0020] The glass substrate of the present invention preferably has a thickness of 0.01 to 1.0 mm.

[0021] The method for producing a glass substrate of the present invention is characterized in that the above-mentioned glass is produced by a fusion method, a down-draw method, or a float method. Effect of the Invention

[0022] According to the present invention, it is possible to provide a glass substrate having low electrostatic charge. [Brief description of the drawings]

[0023] [Figure 1] FIG. 2 is an explanatory diagram for explaining a method for measuring a thermal shrinkage rate. [Diagram 2]These are the electrostatic measurement results for glasses A, B, and C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The glass substrate of the present invention is characterized in that the glass composition contains, in mass %, 0.03% or less Li2O, 0.001 to 0.1% Na2O, and 0.001 to 1% K2O, with the mass ratio Na2O / K2O being less than 1. The reasons for limiting the content of each component as described above are as follows. In the explanation of the content of each component, % denotes mass % unless otherwise specified.

[0025] Li is the smallest element among alkali metals. Therefore, Li is easily mobile in glass and contributes most to the diffusion of electric charges. Therefore, Li can be said to be the most effective element in terms of reducing electrostatic charge. However, because of its ease of movement, Li is most likely to diffuse into the semiconductor material during the TFT fabrication process, including heat treatment, and tends to reduce the performance of the TFT. Therefore, the content of Li2O is preferably 0.03% or less, 0.02% or less, 0.01% or less, 0.005% or less, 0.001% or less, and particularly 0.0005% or less.

[0026] Among alkali metals, Na has the second largest contribution to charge diffusion after Li. It is also the second most likely to diffuse into semiconductor materials during the TFT fabrication process after Li. Therefore, since Na reduces the chargeability and is less likely to reduce the performance of the TFT than Li, it is preferable to contain more Na2O than Li2O. Specifically, the preferred upper limit of Na2O content is 0.1%, 0.09%, 0.08%, 0.07%, and particularly 0.06%, and the preferred lower limit of Na2O content is 0.001%, 0.005%, 0.01%, 0.02%, and particularly 0.03%.

[0027] K has a larger ionic radius than Li and Na and is less mobile in glass, but since charging occurs on the outermost surface of the glass substrate, even K, which is less mobile, can sufficiently diffuse the charge and reduce the charging property. Furthermore, since K is less likely to deteriorate the performance of the TFT than Li and Na, it is preferable to contain more K2O than Li2O and Na2O. Specifically, the preferred upper limit of the K2O content is 1%, 0.9%, 0.8%, 0.7%, 0.6%, and particularly 0.4%, and the preferred lower limit of the K2O content is 0.001%, 0.01%, 0.1%, 0.15%, 0.2%, 0.25%, and particularly 0.3%.

[0028] Furthermore, Na becomes less mobile when it is co-contained with K. In order to further reduce the electrostatic charge and prevent the TFT performance from deteriorating, Na2O / K2O is preferably 1.0 or less, 0.9 or less, 0.8 or less, 0.7 or less, and particularly preferably 0.6 or less.

[0029] Table 1 shows the alkali contents of glasses A, B and C.

[0030] [Table 1]

[0031] Figure 2 shows the electrostatic charge measurement results for glasses A, B, and C. It can be seen from Figure 2 that the surface potential of glass B, which contains a large amount of K2O, drops significantly over time. Glasses A, B, and C can be used in the TFT process, and it can be seen that specifying the amount of alkali is extremely effective in reducing electrostatic charge.

[0032] In addition to the above components, the following components may also be included:

[0033] B2O3 is a component that enhances melting properties and devitrification resistance. On the other hand, it lowers the strain point and Young's modulus, which increases the thermal shrinkage rate and makes pitch deviation more likely to occur during the panel manufacturing process. Therefore, the content of B2O3 is preferably 9% or less, 8% or less, 7% or less, 6% or less, 5% or less, 4% or less, 3% or less, and especially 2% or less.

[0034] TiO2 has the effect of improving the Young's modulus. On the other hand, it may deteriorate the devitrification resistance and cause coloring of the glass. Therefore, the TiO2 content is preferably 2% or less, 1% or less, 0.5% or less, and particularly preferably 0.1% or less.

[0035] SiO2 is a component that forms the skeleton of glass, increases the strain point, and enhances acid resistance. On the other hand, if the SiO2 content is high, the high-temperature viscosity increases, melting property decreases, devitrified crystals such as cristobalite tend to precipitate, and the liquidus temperature increases. In addition, the etching rate by HF decreases. Therefore, the SiO2 content is preferably 55 to 70%, 58 to 65%, and particularly 59 to 62%.

[0036] Al2O3 is a component that forms the glass skeleton, increases the strain point, and further increases the Young's modulus. On the other hand, if the content of Al2O3 is high, devitrified crystals of mullite and feldspar tend to precipitate, and the liquidus temperature becomes high. Therefore, the content of Al2O3 is preferably 8 to 30%, 15 to 25%, 17 to 23%, 18 to 22%, 18 to 21%, and particularly preferably 18 to 20%.

[0037] MgO is a component that reduces high-temperature viscosity, improves melting property, and increases Young's modulus. On the other hand, if the content of MgO is high, it promotes crystal precipitation of mullite, Mg, Ba-derived crystals, and cristobalite. It also significantly lowers the strain point. Therefore, the content of MgO is preferably 0 to 10%, 2 to 6%, 2 to 5%, 2.5 to 5%, and particularly preferably 2.5 to 4.5%.

[0038] CaO is a component that reduces high-temperature viscosity and significantly improves melting property without lowering the strain point. CaO is a component that reduces raw material costs because the raw materials introduced are relatively inexpensive among alkaline earth metal oxides. It is also a component that increases Young's modulus. CaO has the effect of suppressing the precipitation of devitrified crystals containing Mg. On the other hand, if the CaO content is high, anorthite devitrified crystals are likely to precipitate and the density is likely to increase. Therefore, the CaO content is preferably 0 to 10%, 2 to 8%, 3 to 7%, 3.5 to 6%, and particularly 3.5 to 5.5%.

[0039] MgO / CaO is an important component ratio for achieving both high devitrification resistance and high specific Young's modulus. If MgO / CaO is small, the specific Young's modulus is likely to decrease. On the other hand, if MgO / CaO is large, the liquidus temperature is likely to increase due to devitrification crystals containing Mg. Therefore, MgO / CaO is preferably 0 to 3, 0.4 to 1.5, 0.5 to 1.0, 0.5 to 0.9, and particularly preferably 0.6 to 0.8. Here, "MgO / CaO" is the value obtained by dividing the content of MgO by the content of CaO.

[0040] SrO is a component that suppresses phase separation and improves devitrification resistance. Furthermore, it is a component that lowers high-temperature viscosity and improves melting property without lowering the strain point. On the other hand, if the SrO content is high, in a glass system that contains a lot of CaO, feldspar-based devitrification crystals are likely to precipitate, and devitrification resistance is likely to decrease. Furthermore, there is a tendency for the density to increase and the Young's modulus to decrease. Therefore, the SrO content is preferably 0 to 15%, 0 to 10%, 0 to 5%, 0 to 4%, 0 to 3%, 0 to 2%, 0 to 1.5%, 0 to 1%, and particularly preferably less than 0 to 1%.

[0041] Among alkaline earth metal oxides, BaO is a component that is highly effective in suppressing the precipitation of devitrified crystals of mullite and anorthite. On the other hand, if the BaO content is high, the density increases, the Young's modulus decreases, and the high-temperature viscosity becomes too high, which decreases the melting property. Therefore, the BaO content is 0 to 15%, 6 to 12%, 7 to 11%, 8 to 10.7%, and particularly 9 to 10.5%.

[0042] Alkaline earth metal oxides are very important components for increasing the strain point, devitrification resistance, and melting property. If the amount of alkaline earth metal oxide is small, the strain point increases, but it becomes difficult to suppress the precipitation of Al2O3-based devitrification crystals, and the high-temperature viscosity increases, making the melting property more likely to decrease. On the other hand, if the amount of alkaline earth metal oxide is large, the melting property is improved, but the strain point is more likely to decrease, and there is a risk of causing a decrease in liquidus viscosity due to a decrease in high-temperature viscosity. Therefore, it is preferable that MgO+CaO+SrO+BaO is 10 to 40%, 16 to 20%, 17 to 20%, 17 to 19.5%, and particularly 18 to 19.3%. Here, "MgO+CaO+SrO+BaO" means the total amount of MgO, CaO, SrO, and BaO.

[0043] ZnO is a component that enhances meltability, but if a large amount of ZnO is contained, the glass becomes more susceptible to devitrification and the strain point is more likely to decrease. Therefore, the ZnO content is preferably 0 to 5%, 0 to 3%, 0 to 0.5%, and particularly preferably 0 to 0.2%.

[0044] ZrO2, Y2O3, Nb2O5, and La2O3 have the effect of increasing the strain point and Young's modulus. However, if the content of these components is high, the density tends to increase. Therefore, the content of ZrO2, Y2O3, Nb2O5, and La2O3 is preferably 0 to 5%, 0 to 3%, 0 to 1%, and 0 to less than 0.1%, and particularly preferably 0 to less than 0.05%, respectively.

[0045] SnO2 is a component that has a good clarifying effect in the high temperature range, and also increases the strain point and reduces the high temperature viscosity. On the other hand, if the SnO2 content is high, devitrified crystals of SnO2 tend to precipitate. Therefore, the SnO2 content is preferably 0 to 1%, 0.001 to 1%, 0.01 to 0.5%, and particularly preferably 0.05 to 0.3%.

[0046] As long as the glass properties are not impaired, F2, Cl2, SO3, C, or metal powders such as Al and Si can be added as fining agents up to 5%. CeO2, etc. can also be added as fining agents up to 1%.

[0047] As2O3 and Sb2O3 are effective as clarifiers, and although the glass substrate of the present invention does not completely exclude the introduction of these components, it is preferable to avoid using these components as much as possible from an environmental viewpoint. Furthermore, if a large amount of As2O3 is contained in the glass, the solarization resistance tends to decrease, so it is preferable that the content is 0.1% or less, and in particular that it is substantially not contained. Here, "substantially not containing As2O3" refers to the case where the content of As2O3 in the glass composition is less than 0.05%. In addition, it is preferable that the content of Sb2O3 is 0.2% or less, 0.1% or less, and in particular that it is substantially not contained. Here, "substantially not containing Sb2O3" refers to the case where the content of Sb2O3 in the glass composition is less than 0.05%.

[0048] Fe2O3 is a component that is difficult to avoid as an impurity derived from glass raw materials. Therefore, the introduction of the Fe2O3 component cannot be completely excluded. Since it can also play a role as a clarifier, it may be actively contained, but it is preferable that the glass of the present invention does not contain it as much as possible in order to keep the transmittance of the glass in the ultraviolet range as high as possible. By increasing the transmittance in the ultraviolet range, it is possible to increase the efficiency when using an ultraviolet laser in the customer's process. Specifically, the Fe2O3 content in the glass composition is 0.020% or less, preferably 0.015% or less, more preferably 0.011% or less, and particularly preferably 0.010% or less.

[0049] Cl has the effect of promoting the melting of low-alkali glass, and the addition of Cl can lower the melting temperature and promote the action of the fining agent. It also has the effect of lowering the β-OH value of the molten glass. On the other hand, if the Cl content is high, the strain point is likely to decrease. Therefore, the Cl content is preferably 0.5% or less, particularly 0.001 to 0.2%. In addition, as a raw material for introducing Cl, a chloride of an alkaline earth metal oxide such as strontium chloride, or a raw material such as aluminum chloride can be used.

[0050] The glass substrate of the present invention preferably has the following glass properties.

[0051] The ratio of the surface potential after 300 seconds to the initial surface potential is preferably 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.4 or less, 0.38 or less, 0.36 or less, 0.34 or less, 0.32 or less, and particularly preferably 0.30 or less. In this way, charges are easily diffused from the surface of the glass substrate, and the electrostatic property is reduced, so that defects such as pattern misalignment are less likely to occur.

[0052] The thermal shrinkage rate when heat-treated at 500°C for 1 hour is preferably 30 ppm or less, 20 ppm or less, and particularly preferably 15 ppm or less. In this way, defects such as pattern shifting are less likely to occur. If the thermal shrinkage rate is too low, the production efficiency of the glass substrate is likely to decrease. Therefore, the thermal shrinkage rate is preferably 1 ppm or more, 2 ppm or more, 3 ppm or more, 4 ppm or more, and particularly preferably 5 ppm or more.

[0053] The strain point is preferably 700° C. or higher, 710° C. or higher, and particularly preferably 720° C. or higher. If the strain point is low, the glass substrate is likely to undergo thermal shrinkage during the manufacturing process. There is no particular upper limit to the strain point, but it is preferably 800° C. or lower in consideration of the burden on the manufacturing equipment.

[0054] The average thermal expansion coefficient in the temperature range of 30 to 380°C is 45 x 10 -7 / ℃ or less, 34×10 -7 ~43×10 -7 / ℃, especially 38×10-7 ~41×10 -7 / °C. If the average thermal expansion coefficient in the temperature range of 30 to 380°C is outside the above range, it will not match the thermal expansion coefficient of the surrounding members, and peeling of the surrounding members or warping of the glass substrate will easily occur. In addition, if this value is large, pitch deviation due to temperature unevenness during heat treatment will easily occur.

[0055] The higher the Young's modulus, the less likely the glass substrate is to deform. The Young's modulus is preferably 73 GPa or more, 75 GPa or more, and particularly 77 GPa or more. On the other hand, a composition with a high Young's modulus tends to have poor chemical resistance. Therefore, the Young's modulus is preferably 120 GPa or less, 110 GPa or less, 100 GPa or less, 95 GPa or less, 90 GPa or less, and particularly 88 GPa or less.

[0056] Specific Young's modulus is 29.5 GPa / g cm -3 Ultra, 30GPa / g cm -3 Above, 30.5 GPa / g cm -3 Above, 31GPa / g cm -3 Above, 31.5 GPa / g cm -3 Above 32 GPa / g cm -3 If the specific Young's modulus is high, the glass substrate tends to bend under its own weight.

[0057] The liquidus temperature is preferably less than 1350° C., 1300° C. or less, 1280° C. or less, particularly preferably 1260° C. or less. If the liquidus temperature is high, devitrification crystals are generated during forming by an overflow downdraw method or the like, and the productivity of glass substrates is likely to decrease.

[0058] The liquidus viscosity is 10 4.0 dPa s or more, 10 4.2 dPa s or more, 10 4.4 dPa s or more, 10 4.6 dPa s or more, especially 10 4.8 It is preferable that the liquidus viscosity is dPa·s or more. If the liquidus viscosity is low, devitrification crystals occur during forming using the overflow downdraw method or the like, which tends to reduce the productivity of glass substrates.

[0059] High temperature viscosity 10 2.5 The temperature at dPa·s is preferably 1660°C or less, 1640°C or less, 1630°C or less, particularly preferably 1620°C or less. 2.5 When the temperature at dPa·s becomes high, it becomes difficult to melt the glass, and the manufacturing cost of the glass substrate rises.

[0060] In the glass of the present invention, when the β-OH value is reduced, the strain point can be increased and the thermal shrinkage rate can be significantly reduced. The β-OH value is preferably 0.30 / mm or less, 0.25 / mm or less, 0.20 / mm or less, 0.15 / mm or less, and particularly preferably 0.10 / mm or less. If the β-OH value is too large, the strain point is likely to decrease. If the β-OH value is too small, the melting property is likely to decrease. Therefore, the β-OH value is preferably 0.01 / mm or more, and particularly preferably 0.02 / mm or more.

[0061] The following methods can be used to reduce the β-OH value: (1) Select raw materials with low water content. (2) Add components that reduce the water content in the glass (Cl, SO3, etc.). (3) Reduce the water content in the furnace atmosphere. (4) Bubble N2 in the molten glass. (5) Use a small melting furnace. (6) Increase the flow rate of the molten glass. (7) Use an electric melting method.

[0062] Here, the "β-OH value" refers to a value obtained by measuring the transmittance of glass using FT-IR and using the following formula:

[0063] β-OH value = (1 / X)log(T1 / T2) X: Glass thickness (mm) T1: Reference wavelength 3846cm -1 Transmittance (%) T2: Hydroxyl group absorption wavelength 3600cm -1 Minimum transmittance (%) near

[0064] The etching rate by HF is preferably 0.8 μm / min or more, 0.9 μm / min or more, particularly 1 μm / min or more. If the etching rate by HF is low, it becomes difficult to thin the glass substrate in the slimming process. Here, the "etching rate by HF" refers to a value calculated from the etching depth when a part of the mirror-polished glass surface is masked with polyimide tape and then etched with a 5 mass % HF aqueous solution at 20°C for 30 minutes.

[0065] The glass substrate of the present invention is preferably flat and has an overflow joining surface at the center in the thickness direction. In other words, it is preferably formed by the overflow down-draw method. The overflow down-draw method is a method in which molten glass is made to overflow from both sides of a wedge-shaped refractory, and the overflowed molten glass is stretched downward while joining at the lower end of the wedge to form a flat plate. In the overflow down-draw method, the surface to be the surface of the glass substrate does not contact the refractory and is formed in a free surface state. For this reason, an unpolished glass substrate with good surface quality can be produced at low cost, and it is easy to make the glass substrate large in area and thin in thickness.

[0066] In addition to the overflow downdraw method, it is also possible to form a glass substrate by, for example, a slot down method, a redraw method, a float method, or a roll out method.

[0067] The thickness of the glass substrate is not particularly limited, but in order to facilitate weight reduction of the device, it is preferably 1.0 mm or less, 0.5 mm or less, 0.4 mm or less, 0.35 mm or less, and particularly 0.3 mm or less. On the other hand, if the thickness is too small, the glass substrate is easily bent. Therefore, it is preferable that the thickness of the glass substrate is 0.001 mm or more, and particularly 0.01 mm or more. The thickness can be adjusted by the flow rate and sheet drawing speed during glass production.

[0068] Next, a method for manufacturing a glass substrate will be described.

[0069] The manufacturing process of a glass substrate generally includes a melting process, a fining process, a supplying process, a stirring process, and a forming process. The melting process is a process of melting a glass batch prepared by mixing glass raw materials to obtain molten glass. The fining process is a process of fining the molten glass obtained in the melting process by using a fining agent or the like. The supplying process is a process of transferring the molten glass between each process. The stirring process is a process of stirring and homogenizing the molten glass. The forming process is a process of forming the molten glass into a flat glass. If necessary, a process other than the above, for example, a condition adjusting process of adjusting the molten glass to a state suitable for forming, may be incorporated after the stirring process.

[0070] Conventionally, low-alkali glass is generally melted by heating with a combustion flame of a burner when it is produced industrially. The burner is usually arranged above the melting furnace, and a fossil fuel, specifically a liquid fuel such as heavy oil or a gaseous fuel such as LPG, is used as the fuel. The combustion flame can be obtained by mixing a fossil fuel with oxygen gas. However, in this method, a lot of moisture is mixed into the molten glass during melting, so that the β-OH value is likely to increase. Therefore, in producing the glass of the present invention, it is preferable to perform electrical heating with a heating electrode, and it is preferable to melt the glass by electrical heating with a heating electrode without heating with a combustion flame of a burner. This makes it difficult for moisture to be mixed into the molten glass during melting, so that the β-OH value is easily reduced. Furthermore, when electrical heating with a heating electrode is performed, the amount of energy per mass required to obtain molten glass is reduced, and the amount of melted volatile matter is reduced, so that the environmental load can be reduced.

[0071] The electrical heating by the heating electrode is preferably carried out by applying an AC voltage to the heating electrode provided at the bottom or side of the melting furnace so as to be in contact with the molten glass in the melting furnace. The material used for the heating electrode is preferably one that has heat resistance and corrosion resistance against the molten glass, and for example, tin oxide, molybdenum, platinum, rhodium, etc. can be used, and molybdenum is particularly preferable.

[0072] The glass substrate of the present invention is a low-alkali glass that does not contain a large amount of alkali metal oxides, and therefore has a high electrical resistivity. Therefore, when applying electrical heating using a heating electrode to low-alkali glass, there is a risk that the current will flow not only to the molten glass but also to the refractory material constituting the melting furnace, causing early damage to the refractory material constituting the melting furnace. In order to prevent this, it is preferable to use a zirconia-based refractory material with high electrical resistivity, particularly electrocast zirconia bricks, as the furnace refractory material, and further, it is preferable that the content of ZrO2 in the zirconia-based refractory material is 85 mass% or more, particularly 90 mass% or more. EXAMPLES

[0073] The present invention will now be described with reference to examples.

[0074] Tables 2 and 3 show examples of the present invention (samples No. 1 to 23) and a comparative example (sample No. 24). In the tables, "NA" means that the measurement was not performed.

[0075] [Table 2]

[0076] [Table 3]

[0077] First, a glass batch prepared by mixing glass raw materials to obtain the glass composition shown in the table was placed in a platinum crucible and melted at 1600 to 1650°C for 24 hours. When melting the glass batch, a platinum stirrer was used to stir and homogenize the glass. Next, the molten glass was poured onto a carbon plate and formed into a plate shape, and then slowly cooled for 30 minutes at a temperature near the annealing point. For each sample obtained, the surface potential after 300 seconds / initial surface potential, thermal contraction rate, strain point Ps, annealing point Ta, softening point Ts, average thermal expansion coefficient α in the temperature range of 30 to 380°C, density, Young's modulus, specific Young's modulus, liquidus temperature TL, liquidus viscosity logηatTL, ​​high-temperature viscosity 10 4.5 Temperature in dPa·s, high temperature viscosity 10 4.0Temperature in dPa·s, high temperature viscosity 10 3.0 Temperature in dPa·s, high temperature viscosity 10 2.5 The temperature in dPa·s was evaluated.

[0078] The surface potential after 300 seconds / initial surface potential was measured by the method described above.

[0079] The heat shrinkage rate was measured by the method described above.

[0080] The strain point Ps, annealing point Ta, and softening point Ts are values ​​measured based on the methods of ASTM C336 and C338.

[0081] The average thermal expansion coefficient α in the temperature range of 30 to 380° C. is a value measured with a dilatometer.

[0082] The density is a value measured according to the well-known Archimedes method.

[0083] The Young's modulus is a value measured using a well-known resonance method. The specific Young's modulus is the value obtained by dividing the Young's modulus by the density.

[0084] The liquidus temperature TL is the temperature at which crystals (primary phase) precipitate when a glass powder that passes through a standard 30 mesh sieve (sieve opening 500 μm) and remains on a 50 mesh sieve (sieve opening 300 μm) is placed in a platinum boat and held in a temperature gradient furnace for 24 hours.

[0085] liquidus viscosity log 10 ηTL is the viscosity of the glass at the liquidus temperature TL measured by the platinum ball pull-up method.

[0086] High temperature viscosity 10 4.5 dPa·s, 10 4.0 dPa·s, 10 3.0 dPa s and 10 2.5 The temperature in dPa·s was measured by the platinum sphere pulling method.

[0087] As is clear from the table, samples No. 1 to No. 23 have low electrostatic potential, with the ratio of surface potential after 300 seconds to the initial surface potential being 0.74 or less, and are considered suitable for use as substrates for organic EL displays, etc. On the other hand, sample No. 24 had a low KO content, and therefore had high electrostatic potential, with the ratio of surface potential after 300 seconds to the initial surface potential being 0.87.

[0088] For reference, other examples of glass compositions for the glass substrate of the present invention are shown in Tables 4 and 5.

[0089] [Table 4]

[0090] [Table 5]

Claims

1. The glass composition is, in mass%, SiO 2 55-70%, Al 2 O 3 8-30%, B 2 O 3 4.6% or less, MgO 0-10%, CaO 0-10%, SrO 0-15%, BaO 0.5-15%, Li 2 O 0.02% or less, Na 2 O 0.001-0.1%, K 2 O 0.001 to 1% and, by mass ratio, Na 2 O / K 2 A glass substrate having a thickness of less than 1.

2. The glass composition is, in mass%, TiO 2 2. The glass substrate according to claim 1, wherein the content is 2% or less.

3. 3. The glass substrate according to claim 1, wherein a ratio of surface potential after 300 seconds to the initial surface potential is 0.8 or less.

4. 4. The glass substrate according to claim 1, which has a thermal shrinkage rate of 30 ppm or less when subjected to a heat treatment at 500° C. for 1 hour.

5. 5. The glass substrate according to claim 1, wherein the strain point is 700° C. or higher.

6. The average thermal expansion coefficient at 30 to 380°C is 45 x 10 -7 6. The glass substrate according to claim 1, wherein the temperature is 0.15 to 1.5° C. or less.

7. 7. The glass substrate according to claim 1, wherein the Young's modulus is 73 GPa or more.

8. Liquidus viscosity is 10 4.0 8. The glass substrate according to claim 1, having a viscosity of dPa·s or more.

9. 9. The glass substrate according to claim 1, wherein the β-OH value is 0.30 / mm or less.

10. 10. The glass substrate according to claim 1, wherein the thickness of the glass substrate is 0.01 to 1.0 mm.

11. A method for producing a glass substrate, comprising producing the glass substrate according to any one of claims 1 to 10 by an overflow downdraw method.

Citation Information

Patent Citations

  • Glass for substrate for electronic device

    JP1988176332A

  • Glass and method for producing the same

    JP2006265001A

  • glass

    JP2018100208A

  • Glass composition and process for producing glass composition

    WO2007020824A1

  • Glass

    WO2016194693A1